Factors Associated with Emergency Medical Service Reattendance in Low Acuity Patients Not Transported by Ambulance. (2nd January 2022) - Todd, Verity F.; Swain, Andy; Howie, Graham; Tunnage, Bronwyn; Smith, Tony; Dicker, Bridget
Abstract: Background: The decision for emergency medical services (EMS) personnel not to transport a patient is challenging: there is a risk of subsequent deterioration but transportation of all patients to hospital would overburden emergency departments. The aim of this large-scale EMS study was to identify factors associated with an increased likelihood of ambulance reattendance within 48 hours in low acuity patients who were not transported by ambulance. Methods: We conducted a 2-year retrospective cohort study using data from the St John New Zealand EMS between 1 July 2016 and 30 June 2018 to investigate demographic and clinical associations with ambulance reattendance. Results: In total, 83, 171 low acuity patients not transported by ambulance were included, of whom 4, 512 (5.4%) had an EMS ambulance reattend within 48 hours. There were significant associations between EMS reattendance and patient age, sex, ethnicity, deprivation, and event location. Patients aged 60-74 years old had the highest likelihood of ambulance recall (OR 2.87, 95% CI: 2.51-3.28). Males were more likely to have an EMS ambulance reattend within 48 hours (OR 1.17, 95% CI: 1.09-1.25). Māori and Pacific Peoples had a similar likelihood of EMS recall to European/Others; however, the Asian cohort showed a reduced likelihood of reattendance (OR 0.76, 95% CI: 0.62-0.93). There were significant associations between EMS reattendance and non-transport reason, time spent on scene, event type, clinical acuity level (status), and pain score. Shorter (<30 minutes) on scene times were associated with a decreased likelihood of ambulance reattendance, whereas longer scene times (>45 minutes) were associated with an increased likelihood. Medical events were more likely to require reattendance than accident-related events (OR 1.22, 95% CI: 1.13-1.32). Non-transported patients with a severe pain score (7-10/10) were at increased likelihood of requiring reattendance (OR 1.60, 95% CI: 1.33-1.92). Discussion: The overall low rate of EMS reattendance is encouraging. Further research is needed into the clinical presentation of patients requiring ambulance reattendance within 48 hours to determine if there are early warning signs indicative of subsequent deterioration.